Impact of green human resource management practices on hotels environmental performance: A mediation and moderation analysis - Adnan Ahmed Sheikh; Ali Shan; Nadir Munir Hassan; Sajjad Nawaz Khan; Amani AbdAlatti (Sustainable Futures)
With the unprecedented surge in environmental concerns, this study examines the effects of GHRM on EP, OCBE's mediating role, and GOC's moderating role utilizing the AMO model and SE theory. A PLS-SEM analysis was performed on 292 managerial-level staff of 4 to 5-star hotels in Pakistan, acquired using purposive sampling. The results were compelling: GHRM practices including GT, GR, and GOC strongly predicted OCBE. While OCBE mediated the relationship. Likewise GT, GR, and OCBE, GOC positively moderated. This study is one of the few empirical studies to integrate green human resource practices, environmental performance, and organizational citizenship behavior towards environment. It adds to the growing body of research on green HR practices, OCBE, and environmental performance. The study indicates GHRM practices promote OCBE and environmental performance. To address the developing environmental issues in the hotel business, the study suggests that practitioners encourage OCBE through GHRM methods to achieve sustainable performance results.